Studying and Treatment of Outpatients with Bronchitis at The Polyclinic №3 of the City of Urgench, Khorezm Region - Yòldosheva Gulnoza Zokir qizi; Xamidova Gulnoz (Scholars Digest Publishing, 2023)
Abstract for various reasons, in the last decade there has been a tendency to increase the incidence of acute bacterial bronchitis. This pathology is included in the list of ten conditions that require the greatest costs for treatment. Adverse changes in the environment, air pollination, increased amounts of pollutants, and increased pollen Allergy are additional etiopathogenetic factors in bacterial bronchitis.
Keywords: bronchitis, tracheitis, infection, bacteria, inflammation, relapses.